2013
DOI: 10.1364/oe.21.023345
|View full text |Cite
|
Sign up to set email alerts
|

Phase retrieval for object and probe using a series of defocus near-field images

Abstract: Full field x-ray propagation imaging can be severely deteriorated by wave front aberrations. Here we present an extension of ptychographic phase retrieval with simultaneous probe and object reconstruction suitable for the near-field diffractive imaging setting. Update equations used to iteratively solve the phase problem from a set of near-field images in view of reconstruction both object and probe are derived. The algorithm is tested based on numerical simulations including photon shot noise. The results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 45 publications
(36 reference statements)
0
27
0
Order By: Relevance
“…A detailed description of NFP can be found in earlier publications [14,76]. The preprocessing steps for the NFP are as follows: The holograms were dark field corrected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed description of NFP can be found in earlier publications [14,76]. The preprocessing steps for the NFP are as follows: The holograms were dark field corrected.…”
Section: Resultsmentioning
confidence: 99%
“…5.1. This is to be compared to established near-field ptychographic schemes, which are based on lateral [13,154] and/or longi- tudinal translations of the object [14,76]. Hence, the standard approaches require sequential recordings and significantly more input data.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…the approximated source size. In this context, promising algorithms for the simultaneous reconstruction of the empty beam ι 0 and the object function by taking intensity measurements at several distances have been proposed recently [36,64]. Figures 2.7 and 2.8 also illustrate that in order to predict the reconstruction's quality the error value δ max has to be considered in relation to the hologram's contrast.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…If longitudinal diversity is of such importance for near-field imaging, what is the purpose of lateral diversity in this context? We have shown that simultaneous phase retrieval of an object and a non-uniform probe is not possible by exclusively using on-axis shifts [82]. We will see that lateral translations of the object are important for a successful reconstruction of the probe -unperturbed by twin image artifacts.…”
Section: Longitudinal Diversity As a Solution To The Twin Image Problmentioning
confidence: 89%